‘‘Naked’’ TiO2 capsulated in nanovoid microcapsule of poly(vinylidene fluoride) supporter with enhanced photocatalytic activity - Zhang, Y.; Zhang, G.; Liu, Shaomin; Zhang, C.; Xu, X. (Elsevier BV, 2012)
In the field of photocatalytic dyes purification, the immobilization of TiO2 photocatalysts in polymericsupporters with high photocatalytic activity and mass transfer is still an important challenge. In thispaper, pre-synthesized TiO2 (core)/oleic acid (OA) (shell) particles, denoted as TiO2/OA, was doped to poly(vinylindene fluoride) (PVdF) supporters and then irradiated under UV light to construct a novelcomplex, denoted as NTiP composites. Characterization of samples by FT-IR and SEM demonstrates NTiP composites are successfully fabricated. The average pore size and the BET surface area of NTiP composites obtained by BET method are, respectively. Additionally, the methyl orange adsorption and photocatalytic tests of NTiP composites present relatively outstanding results compared to TiO2 directly fixed to PVdF material, denoted as TiP composites, which demonstrate that the nanovoid layer between TiO2 particle and PVdF material left by UV irradiation could effectively liberate all the active sites of TiO2 particles and promote the mass transfer and photocatalytic activity. Therefore, NTiP composites as a novel TiO2-immobilized structure will have a promising application in the recovery of TiO2 catalyst with antidecomposed polymeric material.